2023
DOI: 10.3390/cancers15235693
|View full text |Cite
|
Sign up to set email alerts
|

Increased Plasmatic Levels of Exosomes Are Significantly Related to Relapse Rate in Patients with Oral Squamous Cell Carcinoma: A Cohort Study

Samuel Rodríguez-Zorrilla,
Alejandro I. Lorenzo-Pouso,
Stefano Fais
et al.

Abstract: Background: Oral squamous cell carcinoma (OSCC) is characterized by an immunosuppressive tumor microenvironment. Their plasma-derived exosomes deliver immunomodulatory molecules and cargo that correlate significantly with clinical parameters. This study aims to assess the exosomal profile as a potential tool for early detection of relapse and long-term outcomes in OSCC patients undergoing conventional therapy. Methods: 27 OSCC patients with a median 38-month follow-up were included in this study. The relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…An independent study performed in patients with glioblastoma reported comparable results in displaying higher exosome levels in the plasma of glioblastoma patients [17]. More recently, a longitudinal study performed using the NTA in patients with oral cancers has shown that high plasmatic levels of exosomes may be predictive of a recurrence after surgical treatment [18], supporting a previous investigation which revealed different exosome counts before and after surgical treatment [19].…”
mentioning
confidence: 57%
See 3 more Smart Citations
“…An independent study performed in patients with glioblastoma reported comparable results in displaying higher exosome levels in the plasma of glioblastoma patients [17]. More recently, a longitudinal study performed using the NTA in patients with oral cancers has shown that high plasmatic levels of exosomes may be predictive of a recurrence after surgical treatment [18], supporting a previous investigation which revealed different exosome counts before and after surgical treatment [19].…”
mentioning
confidence: 57%
“…Of course, the other disease conditions need clinical validation at least comparable to what we have to date for tumor patients. This editorial has emphasized a bulk of clinical results supporting the use of a "plasmatic exosome count" as a new valuable tool in the follow-up of tumor patients [7,[17][18][19][20]. The plasmatic exosome count may be implemented by analyzing other components, including: (i) the exosome size (that has been proven to be smaller in tumor patients than in controls) [16,67]; (ii) the expression of known tumor markers [23][24][25] and (iii) the intraluminal pH of circulating exosomes [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations